Research and Manufacturing of Wrist Joint Rehabilitation Robots Based on the 3-UU Parallel Mechanism - Tian Peiliang; Liu Zhifei; Wang Weibo; Ma Xiaobao; Lan Yuan (Jixie chuandong)
Based on the 3-UU parallel mechanism, a prototype robot for wrist joint rehabilitation is developed to assist stroke patients in wrist joint rehabilitation training. Based on the constraint relation and geometric characteristics of the 3-UU mechanism, the inverse kinematics of 3-UU mechanism is analyzed by spherical coordinate method and roll-pitch-yaw (RPY) method， and the relation between the platform and the driver is obtained. Compared with the classic 3-RRR wrist joint rehabilitation mechanism, the developed prototype has no advantages such as multi-solution and singular value. The motion performance of the prototype and the electromyographic signals of the two major muscle groups in the forearm are measured. The experimental results show that the maximum roll angle is -90° to 90°, the pitch angle is -90° to 90°， and the virtual yaw angle is -180° to 180°. The maximum electromyogram (EMG) signal can be generated at 950 mV. The results show that the developed model can meet the requirements of the wrist motion and train the forearm muscle group.